Quill mites (Acari: Syringophilidae) associated with galliform birds (Aves: Galliformes) - Skoracki, Maciej; Sikora, Bozena (Zootaxa, 2011)
A review of the syringophilid mites (Acari: Prostigmata: Cheyletoidea: Syringophilidae) parasitizing galliform birds is given. Four new species are described: Kalamotrypetes cracidus sp. nov. ex Penelope sp. from Guyana and Ortalis canicollis (Wagler) (Cracidae) from Paraguay; Galliphilopsis colinus sp. nov. ex Colinus cristatus (Linnaeus) from Surinam and C. leucopogon (Lesson) (Odontophoridae) from Colombia; G. szeptyckii sp. nov. ex Coturnix pectoralis Gould from Australia, C. chinensis (Linnaeus) from Indonesia and C. coturnix (Linnaeus) (Phasianidae) from Japan; Columbiphilus odontophoridus sp. nov. ex Colinus leucopogon (Lesson) from Colombia and C. cristatus (Linnaeus) from Surinam. The species K. pavodaptes Casto is transferred to the genus Mironovia Chirov and Kravtsova, and a new diagnosis for the quill mites of the genus Kalamotrypetes Casto is established. New host species are reported: Lagopus lagopus (Linnaeus) from Norway for Mironovia lagopus Bochkov and Skirnisson; Gallus sonneratii Temminck from India for Columbiphilus polonica Skoracki et al., and Alectoris rufa from France for C. alectoris Fain et al. Additionally, a complete check-list and a key to all genera and species of quill mites associated with galliform birds is proposed.